2015
DOI: 10.1063/1.4922631
|View full text |Cite
|
Sign up to set email alerts
|

Control of ion energy distributions using phase shifting in multi-frequency capacitively coupled plasmas

Abstract: Control of ion energy distributions (IEDs) onto the surface of wafers is an ongoing challenge in microelectronics fabrication. The use of capacitively coupled plasmas (CCPs) using multiple radio frequency (rf) power sources provides many opportunities to customize IEDs. In dual-frequency CCPs using a fundamental frequency and its second harmonic, varying the relative voltages, powers, and phases between the fundamental and second harmonic biases have demonstrated potential as control mechanisms for the shape o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 39 publications
0
39
0
Order By: Relevance
“…A diagram of the experimental setup is shown in figure 1. A more complete description of the setup has been given previously by Zhang et al [10].…”
Section: Methodsmentioning
confidence: 99%
“…A diagram of the experimental setup is shown in figure 1. A more complete description of the setup has been given previously by Zhang et al [10].…”
Section: Methodsmentioning
confidence: 99%
“…The ion flux is comparatively insensitive to the change in the phase shift meaning that the two quantities can be controlled independently of one another. Since the original study many investigations have demonstrated this effect through both simulation and experiment and extended it to the use of more than two frequencies to increase the amplitude asymmetry of the waveform [28][29][30][31][32][33][34][35][36][37][38][39][40][41]. It has also been demonstrated that an electrical asymmetry can be generated using sawtooth-like waveforms where the rise and fall times of the voltage waveform differ [41][42][43][44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we demonstrate that Voltage Waveform Tailoring (VWT) i.e. the construction of specific waveform shapes by the summation of multiple rf harmonics [13,14,15,16,17,18,19,20], is capable of disrupting the temporal and spatial symmetries of electron heating in APPs. This, in turn leads to spatio-temporal confinement of the electron heating, and significantly enhanced control of the EEPF.…”
mentioning
confidence: 99%